Advanced pathway engineering for phototrophic putrescine production. Issue 10 (22nd July 2022) - Freudenberg, Robert A.; Wittemeier, Luisa; Einhaus, Alexander; Baier, Thomas; Kruse, Olaf
Summary: The polyamine putrescine (1, 4‐diaminobutane) contributes to cellular fitness in most organisms, where it is derived from the amino acids ornithine or arginine. In the chemical industry, putrescine serves as a versatile building block for polyamide synthesis. The green microalga Chlamydomonas reinhardtii accumulates relatively high putrescine amounts, which, together with recent advances in genetic engineering, enables the generation of a powerful green cell factory to promote sustainable biotechnology for base chemical production. Here, we report a systematic investigation of the native putrescine metabolism in C. reinhardtii, leading to the first CO2 ‐based bio‐production of putrescine, by employing modern synthetic biology and metabolic engineering strategies. A CRISPR/Cas9‐based knockout of key enzymes of the polyamine biosynthesis pathway identified ornithine decarboxylase 1 (ODC1) as a gatekeeper for putrescine accumulation and demonstrated that the arginine decarboxylase (ADC) route is likely inactive and that amine oxidase 2 (AMX2) is mainly responsible for putrescine degradation in C. reinhardtii . A 4.5‐fold increase in cellular putrescine levels was achieved by engineered overexpression of potent candidate ornithine decarboxylases (ODCs). We identified unexpected substrate promiscuity in two bacterial ODCs, which exhibited co‐production of cadaverine and 4‐aminobutanol. Final pathway engineering included overexpression of recombinant arginases for improved substrate availability as well as functional knockout of putrescine degradation, which resulted in a 10‐fold increase in cellular putrescine titres and yielded 200 mg/L in phototrophic high cell density cultivations after 10 days.